SWIFTLET FARMING VISUALIZATION USING MICROSOFT VISUAL BASIC 6.0 - Doddy Oktanto; Jalinas, SKom, MM Jalinas, SKom, MM (Jurnal Sistem Informasi, 2003)
This application is made to provide the information required in swiftlet farming. This application was built using Microsoft Visual Basic 6.0 with the intention that this application can display the character of the user interface or in other words can be understood easily by the user (the user).